EVALUASI LENDUTAN BALOK BETON BERTULANG DENGAN PENDEKATAN MATEMATIS: PENERAPAN TEORI EULER–BERNOULLI TERHADAP BATAS KEMAMPUAN LAYAN - Permata, Sherly (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2025)
Accurate prediction of beam deflection is crucial in civil engineering structural design, ensuring both safety and functionality. This study investigates how the physical and material properties of a beam relate to the maximum deflection under various loading conditions. We used an analytical approach, applying classic deflection equations derived from Euler-Bernoulli beam theory, which assumes linear elasticity and small deformations. Our case study features a simply supported beam with a 4000 mm span. It's made of concrete with a 30 MPa compressive strength and reinforced with steel having a 390 MPa yield strength. The analysis includes common loading scenarios like concentrated and uniformly distributed loads to evaluate their impact on deflection. The calculations show a maximum deflection of 18.78 mm, which exceeds the allowable limit of 14.17 mm set by SNI 2847:2019. This study demonstrates that mathematical models reliably estimate structural behavior and are effective for design decision-making. These findings highlight the importance of analytical proficiency in structural engineering, especially during initial design and assessment phases. Integrating theoretical models with practical data improves the accuracy of structural analysis, contributing to safer and more efficient construction practices.